2018
DOI: 10.1159/000490623
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Silodosin and Tamsulosin in Expectant Therapy of Distal Ureteral Stones

Abstract: Objective: To compare the efficacy and safety of silodosin against tamsulosin as medical expulsion therapeutic agent in stone lower 1/3rd ureter. Patients and Methods: One hundred fifty patients divided equally into 2 groups I and II received silodosin 8 mg and tamsulosin 0.4 mg respectively. Patients aged 18 years or older having single unilateral stone 10 mm or less were included in the study. Patients with bilateral or multiple stones, marked hydronephrosis, previous open or endoscopic surgery and having ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…El-Galaly et al [11] reported that the stone expulsion rate in their series on adult patients was significantly higher in the silodosin group in contrast to the tamsulosin group (83 vs. 57%) and this was also associated with a significantly shorter mean expulsion time in the silodosin group (13.3 ± 4.1 vs. 16.7 ± 5.2 days in the silodosin group and tamsulosin group, respectively). Similarly, in another study on adult patients, silodosin showed a statistically significant higher efficacy regarding stone expulsion rate and time versus tamsulosin (82.4 vs. 61.5%) and (9.4 ± 3.8 vs. 12.7 ± 5.1 days), respectively [29]. This is in accordance with our results as we reported a statistically significant better expulsion rate (89.3 vs. 74.5%) and shorter mean expulsion time (12.4 ± 2.3 vs. a Group I has a statistically significant difference versus the other 2 groups (p < 0.05).…”
Section: Discussionmentioning
confidence: 64%
“…El-Galaly et al [11] reported that the stone expulsion rate in their series on adult patients was significantly higher in the silodosin group in contrast to the tamsulosin group (83 vs. 57%) and this was also associated with a significantly shorter mean expulsion time in the silodosin group (13.3 ± 4.1 vs. 16.7 ± 5.2 days in the silodosin group and tamsulosin group, respectively). Similarly, in another study on adult patients, silodosin showed a statistically significant higher efficacy regarding stone expulsion rate and time versus tamsulosin (82.4 vs. 61.5%) and (9.4 ± 3.8 vs. 12.7 ± 5.1 days), respectively [29]. This is in accordance with our results as we reported a statistically significant better expulsion rate (89.3 vs. 74.5%) and shorter mean expulsion time (12.4 ± 2.3 vs. a Group I has a statistically significant difference versus the other 2 groups (p < 0.05).…”
Section: Discussionmentioning
confidence: 64%
“…Among 2 RCTs, which compared tamsulosin with silodosin, it was found that silodosin was better in expulsion rate and time. [6,23] but expulsion time contrasted by the studies regulated by Elgalaly H et al and Imperatore V et al [12,24]. The study conducted by Shabana W et al showed that combination therapy of tamsulosin and methylprednisolone is better than monotherapy with tamsulosin.…”
Section: Resultsmentioning
confidence: 98%
“…The drugs used to reduce ureter spasms are calcium antagonists (nifedipine), α1-blockers, and β-adrenergic agonists [7,10,12,22,23].…”
Section: Discussionmentioning
confidence: 99%